Paleomagnetism and magnetic fabric of Middle Jurassic dykes from Western Patagonia, Argentina - Rapalini, Augusto Ernesto (2000)
Jurassic volcanism in Patagonia is widespread. Although associated dyke swarms are conspicuous, they have been almost neglected in previous geologic studies of this region. Radiometric, paleomagnetic and magnetic anisotropy studies are reported from a Middle Jurassic basic to intermediate dyke swarm exposed in the Sierra de Mamil Choique (Western Patagonia) in an area of over 350 km2. Two whole-rock K/Ar determinations indicate that these dykes were intruded at around 170 Ma. An anisotropy of magnetic susceptibility (AMS) study on 15 dykes (74 block samples) shows that they carry different kinds of magnetic fabric (both normal and inverse), apparently governed by compositional differences. A paleomagnetic study of these samples suggests that Ti-poor titanomagnetite is the probable carrier to the characteristic remanence. Mean site characteristic directions pass a reversal test (grade C). A paleomagnetic pole, computed by averaging VGPs from each individual dyke, is situated at 70.2°S, 190.4°E (N = 13, α95 = 9.7°), not substantially apart from other Middle Jurassic poles from South America. Further refinement of the Jurassic South American apparent polar wander path is needed to establish whether or not the Mamil Choique dykes were affected by a small tectonic rotation.